Analysis of Waste Management Policy in Lamongan Regency - Achmad Aufa Anggarda; Kismartini Kismartini; Augustin Rina Herawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The environment is a place where living things carry out their daily activities. Of course, in carrying out these activities, living things need a healthy environment and a comfortable atmosphere. Environmental problems are generally caused by natural events, rapid population growth, overuse of natural resources, industrialization and transportation. One of them is the waste problem. Waste produced by humans has an influence on environmental changes. The implementation of waste management is intended so that waste can be managed properly to create a clean and healthy living environment. This study aims to formulate the best alternative policy as an effort to address the problems of implementing waste management in Lamongan Regency. The research method used is descriptive qualitative method. In formulating policy alternatives using Bridgman and Davies' policy analysis process theory which consists of five stages, namely 1) Formulation of Policy Problems, 2) Formulating Goals and Targets, 3) Identifying Policy Parameters, 4) Finding Policy Alternatives and 5) Deciding Policy Alternatives Selected. The results showed that the implementation of waste management in Lamongan Regency that occurred was a problem of the amount of waste that was increasing from time to time and the amount of waste that was managed could not reach 50% of the total waste. Factors causing the problem are caused by: Inadequate fleet of facilities and infrastructure; Limited budget funds; Inadequate cleaning staff; and the level of public awareness of waste care is still low.